The Effect of Madrasah Diniyah Takmiliyah Awaliyah Learning on the Understanding of Islamic Education Subject in Elementary School - Yugo, Tri; Yunani, Ahmad; Salsabila, Nadira (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study investigates the impact of Diniyah Takmiliyah Awaliyah (MDTA) learning on the comprehension of Islamic religious subjects at Jatimekar State Elementary School in Baleendah District, Bandung Regency. The research addresses the observed differences in religious lesson comprehension between elementary and early education. A quantitative approach with a quasi-experimental model was employed, involving 84 sixth-grade students divided into experimental and control groups. Data was collected through comprehension tests covering PAI material from Chapters 1 to 4 and questionnaires. The analysis revealed that students who participated in MDTA learning had a better understanding of Islamic religious material compared to those who did not. These findings suggest that MDTA learning significantly enhances the comprehension of Islamic religious subjects in elementary schools. The study advocates for stronger synergy between early and formal education to improve the quality of Islamic religious learning. This research aims to inform more effective education policies to enhance the quality of religious education in Indonesia.